Dialektika Injil dan Budaya: Membaca Ulang Kiprah Kiai Sadrach Melalui Lensa Hermeneutik Gadamer - Setiawan, David Eko; Maryanto, Jaka (Sekolah Tinggi Teologi Berita Hidup, 2023)
This study aims to gain a new understanding of Kiai Sadrach's work in addressing the dialectic of the Gospel and culture through Gadamer's hermeneutic lens. The method used in this study is library research and approaches using Gadamer's hermeneutic theory. The research problem in this paper is how is the re-reading of Kiai Sadrach's work in responding to the dialectic of the Gospel and culture. The results of the research are as follows; First, the dialectic of the Gospel and culture in Kiai Sadrach's work has formed a personality that is sensitive and selective towards culture. Second, Sadrach's skill in contextualizing the Gospel is a long process from the Fusion of Horizons from his predecessors who have been active in the dialectic of the Gospel and culture. Third, Sadrach's high appreciation for his culture does not necessarily make him stutter in building relationships with the foreigners around him. Fourth, the living of the faith of the Golongane Wong Kristen community, Kang Mardiko, is a concrete example that the